Te Tiriti o Waitangi/Treaty of Waitangi 1840: its influence on health practice - Wilson, Denise; Haretuku, Riripeti (Cultural safety in Aotearoa New Zealand, 2015)
In this second edition of Cultural Safety in Aotearoa New Zealand, editor Dianne Wepa presents a range of theoretical and practice-based perspectives adopted by experienced educators who are active in cultural safety education. Dianne Wepa, Hawkes Bay District Health Board, NZ.
Keywords: bicultural; health; tiriti o waitangi/treaty of waitangi; treaty principles

Chapter 6: Rangatiratanga and Social Policy - Kawharu, Merata (Waitangi Revisited, 2005)
Keywords: crown policy; education; government relations; hauora; health; history; land tenure; race relations; rangatiratanga; social policy; tiriti o waitangi/treaty of waitangi